Possible Involvement of DNA Methylation in TSC1 Gene Expression in Neuroprotection Induced by Hypoxic Preconditioning. (9th September 2022) - Qi, Ruifang; Xie, Yabin; Zhang, Xiaolu; Jiang, Shuyuan; Liu, Xiaolei; Xie, Wei; Jia, Xiaoe; Bade, Rengui; Liu, You; Gong, Kerui; Yang, Wenjie; Guo, Guanghui; et al.
Abstract : Background . It has been reported that ischemia and ischemic preconditioning (IPC) have different effects on the expression of tuberous sclerosis complex 1 (TSC1), which may contribute to the tolerance to ischemia/hypoxia with the increase of autophagy. The mechanisms of TSC1 differential expression are still unclear under ischemia/IPC conditions in hippocampal Cornu Ammon 1 (CA1) and Cornu Ammon 3 (CA3) area neuronal cells. While we have shown that 5-Aza-CdR, a DNA methyltransferase inhibitor, can upregulate TSC1 and increase hypoxic tolerance by autophagy in vivo and in vitro, in this study, we examined whether DNA methylation was involved in the differential expression of TSC1 in the CA1 and CA3 regions induced by hypoxic preconditioning (HPC). Methods . Level of rapamycin (mTOR) autophagy, a downstream molecular pathway of TSC1/TSC2 complex, was detected in HPC mouse hippocampal CA1 and CA3 areas as well as in the HPC model of mouse hippocampal HT22 cells. DNA methylation level of TSC1 promoter (-720 bp -360 bp) was determined in CA1 and CA3 areas by bisulfite-modified DNA sequencing (BMDS). At the same time, autophagy was detected in HT22 cells transfected with GFP-LC3 plasmid. The role of TSC1 in neuroprotection was measured by cell viability and apoptosis, and the role of TSC1 in metabolism was checked by ATP assay and ROS assay in HT22 cells that overexpressed/knocked down TSC1. Results . HPC upregulated the expression of TSC1, downregulated the level of P-mTOR (Ser2448) and P-p70S6K (Thr389), and enhanced the activity of autophagy in both in vivo and in vitro. The increased expression of TSC1 in HPC may depend on its DNA hypomethylation in the promoter region in vivo. HPC also could reduce energy consumption in HT22 cells. Overexpression and knockdown of TSC1 can affect cell viability, cell apoptosis, and metabolism in HT22 cells exposed to hypoxia. Conclusion . TSC1 expression induced by HPC may relate to the downregulation of its DNA methylation level with the increase of autophagy and the decrease of energy demand.